Prospective Analysis of Sustainable Tourism Development in Penglipuran Village as A Tourist Village Role Model in Bali - Ida Bagus Made Sutrisna; Ida Ayu Nyoman Saskara; Made Suyana Utama; Ni Putu Wiwin Setyari (Technium Social Sciences Journal, 2020)
The success of Bali tourism has become a legend in itself when it comes to international tourism. However, there are many very basic problems in the development of tourism in Bali that threaten the sustainability of the development itself. Penglipuran Tourism Village, is one of the tourism objects that physically have a strong concern for the environment, or eco-tourism which is community-based. Indeed, so far Penglipuran Village has been able to be managed and developed into a role model for a tourism village, but it is necessary to be aware of the negative impact of the massively developing tourism. Tourism can damage the joints of rural life. The purpose of this study is to identify key factors in sustainable tourism development in Penglipuran Tourism Village, Bali Province. The data in this study were collected through Focus Group Discussion (FGD). The analysis of this research uses a descriptive exploratory approach and prospective analysis with MICMAC method. The results of the analysis show that there are key factors in sustainable tourism development in Penglipuran Tourism Village, namely the uniqueness of the tourism village, community participation, local customs and culture, village tourism management/packages, promotional and marketing strategies, tourism aid funds, community economy, HR competence. managers, tourist village facilities, and environmental sustainability. the main factors which are the key drivers, namely factors with high influence and low level of dependence, namely local customs and culture factors as well as the competence factor of human resources managers. Given that this study is a continuation study, as a follow-up, it is recommended to continue the study with another prospective analysis.